The Valuation of the Operational Flexibility of the Energy Investment Project Based on a Gas-Fired Power Plant - Dominik Kryzia; Michał Kopacz; Katarzyna Kryzia (Energies, 2020)
This paper presents an attempt to the valuation of the operational flexibility of the energy investment project based on the example of combined cycle gas turbine (CCGT). For this purpose, the real options approach (ROA), net present value (NPV) method, and the Monte Carlo (MC) simulation have been used. Motivations to take up such a topic result from the fact that traditional valuation methods neglect flexibility embedded in CCGT assets. Operational flexibility was defined as the switching option to dynamically shut down and restart gas units. Valuation of the operational flexibility, the project’s extended net present value (XNPV), was based on a discounted cash flow model. The Monte Carlo simulation, allowing for better replication of the stochastic nature of market factors and some technical parameters, was introduced to the valuation model. The obtained results indicate that the value of the options significantly influences the NPV of the analyzed technology and its risk profile. The NPV was calculated at −169.1 million USD, while the XNPV amounted to 102.5 million USD. This difference, compared to the NPV distribution range at a significance level of 0.05, was more than 8.1% (almost 10.4% for α = 0.1). The results achieved help to explain the significance of the operational flexibility in the modeling profitability of CCGT technologies.